Eating NAFTA : trade, food policies, and the destruction of Mexico - Gálvez, Alyshia (California scholarship online., 2018)
"Mexican cuisine has emerged as a paradox of globalization. Food enthusiasts throughout the world celebrate the humble taco at the same time that Mexicans are eating fewer tortillas and more processed food. Today Mexico is experiencing an epidemic of diet-related chronic illness. The precipitous rise of obesity, diabetes, and metabolic disease--all attributed to changes in the Mexican diet--has resulted in a public health emergency. In her gripping new book, Alyshia Gálvez exposes how changes in policy following NAFTA have fundamentally altered one of the most basic elements of life in Mexico - sustenance. Mexicans are faced with a food system that favors food security over subsistence agriculture, development over sustainability, market participation over social welfare, and ideologies of self-care over public health. Trade agreements negotiated to improve lives have sometimes failed, resulting in unintended consequences for people's everyday lives"--Provided by publisher.